GLOBAL SUSTAINABILITY AND POLICY INSTRUMENTS FOR SUSTAINABLE TOURISM DEVELOPMENT OF PAKISTAN - Dr. Muhammad Kamran; Muhammad Dastgeer (Policy Research Journal, 2025)
In this paper, an attempt has been made to identify the opportunities for sustainable tourism development in Pakistan for tourism for environmental conservation, economic development and socio-cultural enhancement. This study assesses the current situation of Pakistan's tourist industry and identifies key problems, such as declining environmental quality, poor infrastructure, and troublesome governance preventing long-term growth. The sustainability implications of the National Tourism Strategy and Vision 2025 are examined in order to determine their efficacy. Based on the study of equivalent examples of countries such as Bhutan, Costa Rica, and Nepal, the paper elaborates on the particular course of action for Pakistan. These are the adoption of sustainability indicators in policy-making, encouragement of ecological tourism, involvement of native communities through skill enhancement and revenue sharing, as well as the use of technology in GIS and digital marketing strategy. Therefore, the a need for cooperation between the public and the private sector as well as proper follow through and implementation of policy and regular assessment to make sure goals are being met. This article also contains recommendations for further research on regional investigation and incorporating renewable energy and digital technologies in tourism management.